CHARACTERISTICS AND EFFECTIVENESS OF DIABETES ONE STOP CLINIC FOLLOW-UP AMONG PATIENTS WITH TYPE 1 DIABETES MELLITUS IN TEMERLOH, PAHANG - LV, Hema; CK, See; JH, Yung; V, Hashini (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Type 1 diabetes (T1D) is commonly diagnosed during childhood or early adulthood. Dealing with the diagnosis is an overwhelming experience. Apart from glycemic control and prevention of diabetic complications, there is an immense need to address emotional fluctuation, dealing with peer pressure, social acceptance and interpersonal relationship. METHODOLOGY This study aims to determine T1D patient characteristics and diabetes control, treatment and diabetes self-care practices after enrolling into a Diabetes One Stop Clinic (DOSC) in Hospital Sultan Haji Ahmad Shah, a tertiary hospital in Temerloh, Pahang. All T1D patients attending DOSC were recruited into the study. Electronic medical records were reviewed for data collection. RESULTS Seventeen (17) patients with T1D were recruited into the study, with mean age of 20.7 (SD 6.7) years old, mean age at diagnosis of 13.8 (SD 5.7) years old and mean duration of diagnosis of 7.1 (SD 4.7) years. There were almost equal number of male and female patients and majority were of Malay ethnicity. Thirteen (13) patients had positive autoantibodies while 4 patients had diabetes diagnosed during childhood with no autoantibody test record. At presentation to DOSC, mean HBA1c was 13.1%. 82.4% (n=14) of patients were on basal bolus regimen and 35.2% (n=6) of patients were on full analogue insulin regimen. At latest follow-up, mean HbA1c had improved to 10.5% with all patients on basal bolus regimen and in 94.1% (n=16) of patients on analogue insulin. Total dose of insulin did not increase significantly from DOSC entry till latest follow-up, but majority of the patients experienced improvement of glycemic control. 41.2% (n=7) had proteinuria or microalbuminuria, while 35.3% (n=6) had deranged liver enzymes. 76.5% (n=13) of patients had adjusted insulin doses according to meal intake and 52.9% (n=9) performed carbohydrate counting. CONCLUSION Provision of Type 1 diabetes care in Temerloh, Pahang is challenging and require a targeted and personalised approach with most patients. Improving glycemic control requires continuous patient engagement and reinforcement during each follow-up.